Tabela de volume para Eucalyptus grandis - de Paula Neto, Francisco; Ribeiro, José Carlos; Ferreira Valente, Osvaldo (Revista Ceres, 2025)
The main purpose of this study was to construct a standard volume table for Fucalyptus grandis, utilizing the combined variable equation, solved by the least, square methods, which takes the form: V = 0,01441 + 0,00337 D2H/100.